Regional trends and drivers of the global methane budget. (27th October 2021) - Stavert, Ann R.; Saunois, Marielle; Canadell, Josep G.; Poulter, Benjamin; Jackson, Robert B.; Regnier, Pierre; Lauerwald, Ronny; Raymond, Peter A.; Allen, George H.; Patra, Prabir K.; Bergamaschi, Peter; Bousquet, Phillipe; et al.
Abstract: The ongoing development of the Global Carbon Project (GCP) global methane (CH4 ) budget shows a continuation of increasing CH4 emissions and CH4 accumulation in the atmosphere during 2000–2017. Here, we decompose the global budget into 19 regions (18 land and 1 oceanic) and five key source sectors to spatially attribute the observed global trends. A comparison of top‐down (TD) (atmospheric and transport model‐based) and bottom‐up (BU) (inventory‐ and process model‐based) CH4 emission estimates demonstrates robust temporal trends with CH4 emissions increasing in 16 of the 19 regions. Five regions—China, Southeast Asia, USA, South Asia, and Brazil—account for >40% of the global total emissions (their anthropogenic and natural sources together totaling >270 Tg CH4  yr −1 in 2008–2017). Two of these regions, China and South Asia, emit predominantly anthropogenic emissions (>75%) and together emit more than 25% of global anthropogenic emissions. China and the Middle East show the largest increases in total emission rates over the 2000 to 2017 period with regional emissions increasing by >20%. In contrast, Europe and Korea and Japan show a steady decline in CH4 emission rates, with total emissions decreasing by ~10% between 2000 and 2017. Coal mining, waste (predominantly solid waste disposal) and livestock (especially enteric fermentation) are dominant drivers of observed emissions increases while declines appear driven by a combination of waste and fossil emission reductions. As such, together these sectors present the greatest risks of further increasing the atmospheric CH4 burden and the greatest opportunities for greenhouse gas abatement. Abstract : Here, we investigate regional trends in the global CH4 budget, looking at drivers of change in total and sector specific CH4  flux using both TD and BU approaches. Most regions show an increase in CH4  fluxes between 2000 and 2007, driven predominantly by coal mining, waste disposal and livestock emissions. In contrast, Europe and the combined Korea and Japan region show a decline in emissions driven by waste and fossil emissions.